2018
DOI: 10.29032/ijhsss.v4.i6.2018.70-88
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Sex-Selection in Nigeria and India

Abstract: The study examined the Nigerian perspective of sex selection visa -vis India's Pre-Conception and Pre-Natal Diagnostic Technique Act, 1994. Sex selection is rampant worldwide despite being prohibited by policies or laws of numerous countries. However, is there a need for prohibition of sex-selection in Nigeria when compared with Indian perspective? The paper adopted both primary and secondary data sources as a means of information. A semi-structured interview of One Hundred (100) participants; fifty (50) Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…12 61-63 For example, there have been concerns about the increasing cultural preference for male child in Nigeria due to social, political and economic reasons. [65][66][67] In the same context, studies have demonstrated that health needs of girls are often neglected. 68 69 Evidence from Asian and African countries [69][70][71][72] suggests societal discrimination against female child as evidenced by gender selective abortions (due to prenatal sex determination).…”
Section: Discussionmentioning
confidence: 99%
“…12 61-63 For example, there have been concerns about the increasing cultural preference for male child in Nigeria due to social, political and economic reasons. [65][66][67] In the same context, studies have demonstrated that health needs of girls are often neglected. 68 69 Evidence from Asian and African countries [69][70][71][72] suggests societal discrimination against female child as evidenced by gender selective abortions (due to prenatal sex determination).…”
Section: Discussionmentioning
confidence: 99%
“…It involves doctrinal research, that is; traditional study of legal propositions associated to contraceptive use in Nigeria, coupled with other information from internet, journals, textbooks, academic websites, and conference proceedings. Similar method was adopted by researchers in discussing their review study (Aina-Pelemo & Saluja, 2018;Tsui et al 2010).…”
Section: Methodsmentioning
confidence: 99%